2018
DOI: 10.1111/febs.14583
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ciliary membrane protein trafficking and signalling by kinesin motor proteins

Abstract: Primary cilia are antenna-like sensory organelles that regulate a substantial number of cellular signalling pathways in vertebrates, both during embryonic development as well as in adulthood, and mutations in genes coding for ciliary proteins are causative of an expanding group of pleiotropic diseases known as ciliopathies. Cilia consist of a microtubule-based axoneme core, which is subtended by a basal body and covered by a bilayer lipid membrane of unique protein and lipid composition. Cilia are dynamic orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 333 publications
(541 reference statements)
0
42
0
7
Order By: Relevance
“…One of these antibodies was able to induce clustering and movement (capping) of its target protein, indicating the ability of at least one other membrane protein, in addition to FMG-1B, to interact with force transduction machinery within the flagellum (data not shown). Similarly, morerecent studies have demonstrated the role of IFT-A complexes in the movement of peripheral as well as integral membrane proteins into the flagellum; the latter include the polycystin 1 and 2 complex, TRPV channels, and various classes of G-protein-coupled receptors (Qin et al, 2005;Huang et al, 2007;Shih et al, 2013;Hirano et al, 2017;Morthorst et al, 2018). There is also evidence that at least some ciliary membrane proteins are not dependent upon IFT for entry into and movement within the ciliary membrane (Ye et al, 2013;Belzile et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these antibodies was able to induce clustering and movement (capping) of its target protein, indicating the ability of at least one other membrane protein, in addition to FMG-1B, to interact with force transduction machinery within the flagellum (data not shown). Similarly, morerecent studies have demonstrated the role of IFT-A complexes in the movement of peripheral as well as integral membrane proteins into the flagellum; the latter include the polycystin 1 and 2 complex, TRPV channels, and various classes of G-protein-coupled receptors (Qin et al, 2005;Huang et al, 2007;Shih et al, 2013;Hirano et al, 2017;Morthorst et al, 2018). There is also evidence that at least some ciliary membrane proteins are not dependent upon IFT for entry into and movement within the ciliary membrane (Ye et al, 2013;Belzile et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Primers flanking the predicted insertion sites were designed using SnapGene (http:// www.snapgene.com/) and synthesized by Integrated DNA Technologies (Skokie, IL). Genomic DNA was isolated from wt, 47, and 56 strains using phenol:chloroform (Newman et al, 1990). Modifications to the protocol were as described at the Chlamydomonas Resource Center (https://www.…”
Section: Genomic Analysismentioning
confidence: 99%
“…Future work with the i3A/i3B motor will allow us to directly determine the ciliary cargoes that depend on KIF3A/KIF3B/KAP activity for import into cilia and/or transport along the axoneme. We will also be able to directly test the roles of kinesin-2 in the steps that lead to ciliogenesis, such as the assembly of the subdistal appendages and the positioning of the basal body [83]. Furthermore, the i3A/i3B motor will be a valuable tool to dissect other dynamic cellular processes in which KIF3A/KIF3B/KAP has been implicated, such as neurite outgrowth in neuronal cells [84].…”
Section: Discussionmentioning
confidence: 99%
“…KIF13B/Gakin is a member of the large Kinesin‐3 family which was previously involved in endosomal transport [Hirokawa et al ., ] as well as in caveolae‐mediated trafficking [Kanai et al ., ]. A role at PC was identified based on the high expression in serum‐starved fibroblasts and was recently extensively reviewed elsewhere [Morthorst et al ., ]. Briefly, KIF13B localises to the BB and axoneme and has been shown to interact with NPHP4, a key component of the transition zone.…”
Section: Pc‐specific Kifmentioning
confidence: 99%